FUND MANAGEMENT STRATEGY BY SCHOOL PRINCIPALS AND SCHOOL ADMINISTRATION EFFECTIVENESS AT STATE HIGH SCHOOL IN GORONTALO PROVINCE - Siswa Ahudulu; Muh Arif; Lamsike Pateda (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to develop artificial intelligence (AI)-based teaching performance and behavior measures to support classroom learning evaluation and management. Using a Research and Development (R&D) approach based on Design-Based Research (DBR), this research was conducted at the Faculty of Tarbiyah and Teacher Training (FTIK) IAIN Gorontalo through four stages: needs analysis, initial model design, limited trials, and improvement evaluation. Data was collected through classroom observations, audio-visual recordings, learning activity logs, and interviews with lecturers and students. The analysis was carried out qualitatively and computationally with pattern recognition and learning analytics techniques using multimodal data. The results of the study produced an annotated audio-visual dataset and a prototype of the Teacher Trainer Dashboard that is able to display indicators of teaching behavior visually, including teacher movements, speech styles, and interaction patterns in the classroom. Initial evaluations by eight researchers showed a positive response to the intuitive and non-judgmental design. This system is considered to be able to support teachers' professional reflection through objective and real-time feedback, without replacing the primary role of educators. Thus, the development of AI-based performance and behavioral measures contributes to the improvement of teacher professionalism and the application of ethical, adaptive, and evidence-based learning analytics in the Islamic education environment.